Design of Supply Chain Performance Measurement in Tawes Fish Breeding Procurement with SCOR Method - Wulandari, Rina Sri; Prakasa, Erwin Fiqih (Journal of Research and Technology, 2023)
Tawes fish is a freshwater fish that has a slightly flattened body shape, a relatively high body, and a short head. Tawes fish or java carp is a fish that is high in animal protein. Tawes has a high enough nutritional content for every 100 g of ingredients such as air (66 g), calories (198 cal), protein (19 g), fat (13 g), and contains calcium, phosphorus, iron, vitamin A and B1 which the human body needs. PT. XYZ is a company that participates in activities in the procurement of goods/services by ministries, institutions or regional apparatus. Suppliers are one of the business partners who play a very important role in ensuring the availability of goods needed by every company when shipping requires a support system, so it uses the Analytical Hierarchy Process (AHP) method and the SCOR method to measure supplier performance. There are 20 key performance indicators (KPI) in this study. Of the 20 KPIs, there are 6 KPIs that get performance in the red category in the traffic light system. These six performances need to be a priority for improvement to improve supply chain performance.